BIODIVERSITY AND CHARACTERISTICS OF CORAL REEF COMMUNITIES IN LY SON MARINE PROTECTED AREA, QUANG NGAI PROVINCE - Ben, Hoang Xuan; Long, Nguyen Van; Tuyen, Hua Thai; Hoang, Phan Kim; Quang, Thai Minh (Vietnam Journal of Marine Science and Technology, 2018)
The result of investigation during September and October 2015 and review of previous studies showed that 224 stony coral species, 232 coral reef fish species, 88 Mollusca and Echinoderm were found in Ly Son Marine Protected Area. The biodiversity of coral reef communities was at medium level compared with other MPAs. The coverage of stony coral and soft coral was 6.1% ± 4.2 SD and 5.6% ± 5.0 SD, respectively. The density of coral reef fishes averaged 121 ± 74.4 SD Ind./100 m2 and this density mainly focused on small size group (< 10 cm) which ocupied 69.6% of total density. The average density of macro-invertebrates was 45 ± 3.0 SD Ind./100 m2 that depended on the Echinoderm group (more than 85% of total density). The coverage of living coral was considered the lowest meanwhile the density of coral reef fishes and macro-invertebrates was at medium level compared with other MPAs. Our result showed that there were two distinguished assemblages of coral reef communities. The charateristics of coral reef fishes and macro-invertebrates communities showed the resemblance in terms of distribution in most of the study sites meanwhile the coral community revealed the separation between two types of communities